Rethinking Islamic Finance: Toward a Hybrid Model - Yudi Ahmad Faisal (Journal of Islamic Thought and Civilization, 2026)
This paper critically reexamines the foundational approaches in the development of Islamic finance by exploring the evolution from idealist to pragmatic and liberal paradigms, and proposes a hybrid model that synthesizes ethical imperatives with economic practicality. The study begins by evaluating the idealist approach, which emphasizes profit-and-loss sharing (PLS) as an Islamic alternative to conventional finance, yet faces challenges in practical implementation. It then explores the pragmatic approach, which adapts classical jurisprudence to modern realities, often relying on debt-based instruments while seeking legitimacy through legal stratagems. The liberal approach, in contrast, interprets riba within a modern context and promotes the integration of Islamic values into existing financial structures without the need for separate institutions. A central contribution of this paper is the elaboration of a hybrid model that balances the maqasid al-Sharī‘ah (objectives of Islamic law) with operational and ethical considerations, supported by examples such as cash waqf linked sukuk, green sukuk (Islamic bonds), musharakah mutanaqisah (diminishing partnership) and takaful (Islamic insurance) cooperative model. This study highlights the necessity of institutional innovation, regulatory flexibility, and contextual interpretation to advance the global relevance and sustainability of Islamic finance. The paper concludes that the hybrid model offers a viable path forward, providing a nuanced framework that reconciles form with substance, tradition with innovation, and Sharī‘ah compliance with socio-economic impact.